The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3945/jn.113.175182
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Insecurity Is Associated with Higher Child Undernutrition in Bangladesh, Ethiopia, and Vietnam, but the Effect Is Not Mediated by Child Dietary Diversity

Abstract: Household food insecurity (HFI) is a recognized underlying determinant of child undernutrition, but evidence of associations between HFI and child undernutrition is mixed. The purpose of this study was to investigate if HFI is associated with undernutrition in children aged 6-59.9 mo in Bangladesh (n = 2356), Ethiopia (n = 3422), and Vietnam (n = 3075) and if child dietary diversity (DD) mediated this effect. We used baseline survey data from the Alive & Thrive project. Logistic regression, adjusting for poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
148
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(186 citation statements)
references
References 17 publications
31
148
5
2
Order By: Relevance
“…This method does not refer to children in particular, but uses country level average numbers of calorie supply and minimum consumption requirements in the population (de Haen, Klasen, & Qaim, 2011). Calorie availability and access are important determinants of child nutritional status (Psaki et al, 2012;Ali et al, 2013). Furthermore, we control for sanitation conditions, which are also important for explaining child nutrition (Fink, Günther, & Hill, 2011;Smith & Haddad, 2014).…”
Section: (C) Control Variablesmentioning
confidence: 99%
“…This method does not refer to children in particular, but uses country level average numbers of calorie supply and minimum consumption requirements in the population (de Haen, Klasen, & Qaim, 2011). Calorie availability and access are important determinants of child nutritional status (Psaki et al, 2012;Ali et al, 2013). Furthermore, we control for sanitation conditions, which are also important for explaining child nutrition (Fink, Günther, & Hill, 2011;Smith & Haddad, 2014).…”
Section: (C) Control Variablesmentioning
confidence: 99%
“…These studies were done among schoolchildren and pre-school children in Columbia (11,12) , tribal children aged 6-59 months in West Bengal, India (13) , children aged 6-18 months living in urban squatter settlements of Karachi, Pakistan (10) and a nationally representative sample of children aged 0-60 months in Brazil (16) . A multinational study from eight countries was done on a sample of 100 children aged 24-60 months in each country (14) and another study included samples ranging from 2356 to 3422 children aged 6-60 months in three countries (9) , but none covered a nationally representative sample of children aged <5 years. In most of the studies, the association of HFI with stunting and underweight was consistent despite different instruments being applied to measure HFI (9)(10)(11)(12)(13)(14)(15) .…”
mentioning
confidence: 99%
“…A multinational study from eight countries was done on a sample of 100 children aged 24-60 months in each country (14) and another study included samples ranging from 2356 to 3422 children aged 6-60 months in three countries (9) , but none covered a nationally representative sample of children aged <5 years. In most of the studies, the association of HFI with stunting and underweight was consistent despite different instruments being applied to measure HFI (9)(10)(11)(12)(13)(14)(15) . However, using level of HFI and/or stunting, wasting, etc.…”
mentioning
confidence: 99%
“…The prevalence of under-five year old children HHFI was also significantly higher in some developing countries, such as, Brazil (51.7%), Ghana (69.9%), Ethiopia (66.4%), Vietnam (40.3%) and Nepal (69.0%). 6,16,18,28 Our study showed that food insecurity was more prevalent among the children of illiterate parents, socio-economically poor families and rural dwelling. The findings were consistent with a study in Nepal that suggested that parent's educational status and socio-economic status were significantly associated with HHFI.…”
Section: Prevalence Of Hhfi (Bivariate Analysis Based On Chisquare Test)mentioning
confidence: 86%
“…Despite impressive progress in agriculture since independence in 1971, food prices have rapidly increased in the last decade which has resulted in poverty and hunger in Bangladesh. 28 In addition, natural hazards, such as, environmental pollution, floods, global worming etc, sometimes hamper agricultural production which may cause HHFI. 34 Bivariate analysis also showed the significant relationship between HHFI and breastfeeding status.…”
Section: Discussionmentioning
confidence: 99%